The Distribution of Inheritance to Extramarital Children on Islamic Legal Perspective : Comparative Study of Islamic Inheritance Law and Constitutional Court Decisions - Tahir, Maulana Amin (Bilancia: Jurnal Studi Ilmu Syariah dan Hukum, 2024)
Children are considered a precious blessing from a higher power and are entrusted to our care to be nurtured and guided towards a bright future. As parents, it is our duty to provide the best possible attention to our children, as protecting their rights is an important obligation outlined in the Islamic religion. Illegitimate children, born to unmarried women, are not exempt from these responsibilities. This study focuses on the distribution of inheritance to illegitimate children in accordance with Islamic law, using a descriptive normative juridical method. The findings reveal that under KHI provisions, an illegitimate child is entitled to a share of their mother's inheritance, with a single woman's child receiving half and a child from multiple women receiving two-thirds.